(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2021)
The current study explores information available about number of egg sacs and spiderlings in 14 lycosid species from Uruguay. We found a positive relationship between female body size and progeny, in agreement with hypotheses that propose that larger body size favors fecundity in spiders.